Coupling Coordination and Prediction Research of Tourism Industry Development and Ecological Environment in China. (19th March 2021) - Yang, Yun; Wang, Rong; Tan, Junlan
Abstract : Based on the data relevant to China's tourism industry and ecological environment from 2005 to 2018, the entropy method and the coupling coordination degree model were used to analyze the coupling degree and coupling coordination degree of the tourism industry's development and the ecological environment, and the GM (1.1) gray model was used to predict these values in the future. The model provided predictions and illustrated the trend in the changes in the degree of coordination between the development of China's tourism industry and the ecological environment for the next five years. The results show the following. (1) The coupling degree between China's tourism industry and the ecological environment was between 0.3 and 0.5. It was in the low-level coupling stage in 2005 and 2006 and generally low in 2005–2009, lower than the average level of 0.4204. In 2018, the coupling degree between the development of China's tourism industry and the ecological environment was mainly in a stage of antagonism, reaching a peak of 0.4998 in 2013. The coupling degree declined slightly from 2013 to 2015 and then began to show an upward trend again in 2016. (2) The average coupling coordination level of China's tourism industry development and ecological environment was 0.4266, which is in the medium coupling coordination stage. From 2007 to 2013, it was mainly in the phase of moderate coupling and coordination and high coupling and coordination from 2014 to 2018. (3) From the prediction results, the coupling degree will enter the coupling degree running-in stage in 2021 and the extreme coordination stage in 2023, but the coupling growth level during the running-in period will be significantly lower than the coupling coordination degree. Coordinated development of the two systems will take a long time, and active economic policies need to be adopted to promote their coordinated development.